1991
DOI: 10.1056/nejm199103283241303
|View full text |Cite
|
Sign up to set email alerts
|

Polymyositis Mediated by T Lymphocytes That Express the γ/δ Receptor

Abstract: Polymyositis can be mediated by gamma/delta T cells. This new form of polymyositis appears to be highly responsive to steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 143 publications
(90 citation statements)
references
References 26 publications
3
85
2
Order By: Relevance
“…The different cell populations can be distinguished only by morphological criteria, i.e., by single-cell analysis. Only in very rare cases of monoclonal expansions (24)(25)(26)(27) can paired TCR chains be identified from tissue homogenates. Early pioneering studies described the Ig repertoire of B cells in single-cell experiments (28), but unbiased amplification from single-tissue-infiltrating T cells has so far been achieved only for TCR ␤-chains (7,8,29).…”
Section: Discussionmentioning
confidence: 99%
“…The different cell populations can be distinguished only by morphological criteria, i.e., by single-cell analysis. Only in very rare cases of monoclonal expansions (24)(25)(26)(27) can paired TCR chains be identified from tissue homogenates. Early pioneering studies described the Ig repertoire of B cells in single-cell experiments (28), but unbiased amplification from single-tissue-infiltrating T cells has so far been achieved only for TCR ␤-chains (7,8,29).…”
Section: Discussionmentioning
confidence: 99%
“…A striking example of a putatively autoimmune human ␥␦-TCR 2 was described in 1991 (8). This ␥␦-TCR was isolated from muscle of a unique but well characterized patient with ␥␦-T cell-mediated myositis.…”
mentioning
confidence: 99%
“…However, other cd TCRs are diverse initially, and later selected during immune responses. 5,6 At the level of lymphocyte populations, the cd TCRs appear to be less evenly distributed than the other adaptive receptors. In mice, where this has been studied in detail, subsets of cd T cells expressing different Vcs become segregated already during ontogeny due to their sequential developmental patterns in the thymus.…”
Section: The CD T-cell Receptorsmentioning
confidence: 99%
“…This amazing story goes back to a rare case of human autoimmune myositis where infiltration of skeletal muscle with cd T cells instead of the more common autoreactive ab T cells was observed. 5 It was found that the muscle-infiltrating cd T cells were clonally expanded and express an uncommon Vc1.3Vd2 1 cd TCR. 86 Based on responses of transfectomas, as well as binding studies with soluble TCR constructs, 87,88 it appears now that this cd TCR (named M88) recognizes a common conformational motif on the surface of several proteins from different species, including bacterial and human aminoacyl-tRNA synthetases.…”
Section: Soluble Proteinsmentioning
confidence: 99%